Babesiose bovina: padronização do teste de ELISA para detecção de anticorpos IgM anti-Babesia bovis e B. bigemina em animais submetidos ao processo de premunição - Patricia Macedo Goncalves (1996)
ELISA tests (biotin/avidin system) using crude antigenic preparations were standardized for the detection of antibodies IgM against B. bovis and B. bigemina. Optimal dilutions of antigens, positive and negative reference sera and conjugate were determined by checkerboard titrations. Serum samples of cattle imported from tick-free areas collected before and during a immunization process were tested. Cut-off values (0,223 e 0,124 for B. bovis e B. bigemina, respectively) were calculated by the mean absorbance of negative sera plus twice their standard deviation. Specfic IgM antibodies against B. bovis iirst appeared at the 11° day post inoculation (p.i.) in animals infested with Booplilus microplus ticks and at the l9° day p.i. in animals which had been inoculated with blood. Antibody titers decreased after day 33, however all animals remainded positive until the end of the experiment (124 days). A similar antibody curve was observed against B. bigemina although the first antibodies were detected at the l4° day p.i. in animals infested with B. micmplus ticks.